Methane dry reforming over copper and iron substituted strontium cobalt oxide perovskite catalyst - Chang, Ying Shi (2016)
With growing concern on global warming arising from greenhouse gases (GHG) emission, dry reforming of methane (DRM) for synthesis gas (syngas) production has emerged as a promising technology by converting the main GHG, methane (CH4) and carbon dioxide (CO2), into hydrogen (H2) and carbon monoxide (CO). Previous research works have been carried out to develop perovskites (ABO3) as reforming catalysts that exhibit high catalytic performance, excellent stability and coke deposition prevention. However, those studies are limited to the common use of perovskite lanthanum nickel-based (LaNiO3) oxides in the DRM reaction. Literature reports that cobalt based catalysts, which are less prone to carbon formation are more active than nickel-based catalysts. Among the various promoters, the substitution of alkaline earth metals such as calcium and strontium for the A-site of perovskites enhances high metallic dispersion and basicity over the catalyst and minimizes carbon formation. In addition, the partial substitution of the „B-site‟ improves the structural stability of perovskites and catalytic performance in methane reforming reactions. Therefore, this work aimed to synthesize and characterize perovskite strontium cobalt-based SrCo0.8M0.2 for DRM reaction where M = iron (Fe) or copper (Cu). These perovskites, SrCo0.8Fe0.2 , SrCo0.8Cu0.2 and SrCo catalysts were prepared via a citrate sol-gel method. Various techniques were then employed to characterize the catalysts such as N2 physisorption, XRD, SEM-EDX and FT-IR. For the kinetics of DRM, the synthesized catalysts were tested in a fixed-bed tubular reactor over a reactant ratio of 1:1 and reforming temperature of 1023 K to obtain the reactant conversion and product yield. From the results obtained, H2:CO product ratios of less than 1.0 were catalytically produced over perovskite strontium cobalt-based SrCo0.8M0.2 oxides. SrCo0.8M0.2 materials were determined as effective perovskite catalysts for methane dry reforming with substantial high methane conversion.